Synthesis and Pancreatic Lipase Inhibitory Activity of Phenacyl Esters of N-Aroyl Amino Acids - Emimmal, Maida Engels S.; Sankar, Veintramuthu (Current Enzyme Inhibition, 2019)
Background: Obesity has become a major life-threatening disorder as it is associated with many risk factors such as coronary heart disease, hypertension, type II diabetes and certain forms of cancer. Pancreatic lipase inhibition is one of the alternate strategies to treat obesity. In our previous study, phenacyl ester of N-sulphonyl beta alanine was obtained as a hit molecule when pharmacophore- based virtual screening was carried out using reported pancreatic lipase inhibitors. Objective: In search of novel pancreatic lipase inhibitors, three series of phenacyl esters of Nsubstituted amino acids were synthesized and evaluated for their pancreatic lipase inhibitory activity. Methods: N-aroylation of amino acids and subsequent esterification with different phenacyl bromides in the presence of N,N-Dimethylformamide (DMF) afforded the corresponding phenacyl esters in quantitative yields. Results: The synthesized compounds were found to have good pancreatic lipase inhibitory activity and showed IC50 in the range of 0.036 and 84 μg/ml. Conclusion: All the synthesized compounds showed better pancreatic lipase inhibitory activity and it indicates that the N-aroylated phenacyl esters could be considered as lead moiety for further studies to develop novel anti-obesity potentials.
Keywords: Amino acids